Artifacts of Cultural Inclusion of People with Physical Disabilities in the Study of the Availability of Historic Sanctuaries. Report on Object-based Photo-ethnography - Borowska-Beszta, Beata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
The presented report on cultural disability studies with the use of photo-ethnography concerns the research of cultural inclusion through the prism of material culture and access artifacts, constructed in 15 historic Marian Sanctuaries of the Kuyavian-Pomeranian Voivodeship, parishioners, pilgrims or tourists with physical disabilities. The research question was: What concept of cultural inclusion of people with physical disabilities is encoded in the artifacts of access ‘to’ and ‘inside’ the sanctuaries? The collected photographic data (944 photographs), textual data, and data from occasional interviews and 2 in-depth interviews collected in 20 months (Jan 2019–Aug 2020) were analyzed using the structural analysis of photography, as well as coding and categorization. Essential element of the research was the theorizing of obtained results and studied categories in the context of theoretical constructs of disability and models. Research results indicated that in 15 historic sanctuaries there are 5 different concepts of cultural inclusion encoded in access artifacts. These are: ‘complete’ cultural inclusion in (4) sanctuaries, ‘almost complete’ in (2), ‘peripheral’ in (4), ‘contradictory’ in (1) and ‘taboo’ in (4). The conclusions from the research indicate that in 11 out of 15 sanctuaries, people with physical disabilities, especially wheelchair users, will need the help of other people (family, friends) to fully benefit from religious or cultural practices in a given sanctuary.